Germany on their Minds : German Jewish Refugees in the United States and their Relationships with Germany, 1938-1988 - Schenderlein, Anne C. (Studies in German History, 2018)
Throughout the 1930s and early 1940s, before closing its borders to Jewish refugees, the United States granted asylum to approximately 90,000 German Jews fleeing the horrors of the Third Reich. And while most became active participants in American society, they also often constructed their individual and communal lives and identities in relation to their home country. As this groundbreaking study shows, even though many refugees wanted little to do with Germany, the political circumstances of the postwar era meant that engagement of some kind was unavoidable—whether initiated within the community itself, or by political actors and the broader public in West Germany. Author Anne C. Schenderlein gives a fascinating account of these entangled histories on both sides of the Atlantic, and demonstrates the remarkable extent to which German Jewish refugees helped to shape the course of West German democratization